2018
DOI: 10.1016/j.bja.2017.11.111
|View full text |Cite
|
Sign up to set email alerts
|

Opioid analgesia and the somatosensory memory of neonatal surgical injury in the adult rat

Abstract: BackgroundNociceptive input during early development can produce somatosensory memory that influences future pain response. Hind-paw incision during the 1st postnatal week in the rat enhances re-incision hyperalgesia in adulthood. We now evaluate its modulation by neonatal analgesia.MethodsNeonatal rats [Postnatal Day 3 (P3)] received saline, intrathecal morphine 0.1 mg kg−1 (IT), subcutaneous morphine 1 mg kg−1 (SC), or sciatic levobupivacaine block (LA) before and after plantar hind-paw incision (three×2 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…5b) after P35 incision compared to WT controls. We then confirmed previous reports (Walker et al, 2009) (Moriarty et al, 2018) that an early life muscle incision (P7) in WT control mice followed by a P35 incision resulted in a longer lasting mechanical hypersensitivity compared to mice with P35 incision alone. Interestingly, if treatment with GH was given at the time of the early life injury (P7), prolonged hypersensitivity was not detected after the second incision (Fig.…”
Section: Gh Sequestering By Infiltrating Macrophages Regulates Incisisupporting
confidence: 90%
See 3 more Smart Citations
“…5b) after P35 incision compared to WT controls. We then confirmed previous reports (Walker et al, 2009) (Moriarty et al, 2018) that an early life muscle incision (P7) in WT control mice followed by a P35 incision resulted in a longer lasting mechanical hypersensitivity compared to mice with P35 incision alone. Interestingly, if treatment with GH was given at the time of the early life injury (P7), prolonged hypersensitivity was not detected after the second incision (Fig.…”
Section: Gh Sequestering By Infiltrating Macrophages Regulates Incisisupporting
confidence: 90%
“…These "priming" effects of neonatal injury have been linked to alterations in the central nervous system (Walker et al, 2016) (Baccei, 2016) (Brewer and Baccei, 2019). However, evidence suggests that there is also a peripheral component that has been less explored (Moriarty et al, 2018). We have shown that the pattern of primary afferent sensitization and injury-related receptor/channel expression in the DRGs after neonatal peripheral injury is unique to that observed in adult nociceptors (Jankowski et al, 2014) (Liu et al, 2017) (Ye and Woodbury, 2010) (Koerber et al, 2010) (Koerber and Woodbury, 2002).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“… 70 , 71 Importantly, prevention by peri-incision local anaesthetic suggests activity-dependent mechanisms that can be modulated by clinically-relevant analgesic interventions. 3 , 72 Although UK paediatric anaesthetists in 1995 reported regular use of opioids and local anaesthetic techniques for neonates requiring surgery, 73 specific data for preterm neonates and this cohort are not available. Additional clinical studies are required to compare the ability of different systemic or regional analgesic techniques to modulate the long-term impact of neonatal surgery.…”
Section: Discussionmentioning
confidence: 99%